2002
DOI: 10.1038/sj.bjp.0704589
|View full text |Cite
|
Sign up to set email alerts
|

NCX‐701 (nitroparacetamol) is an effective antinociceptive agent in rat withdrawal reflexes and wind‐up

Abstract: 1 Non-steroidal anti-in¯ammatory drugs (NSAIDs) are e ective anti-in¯ammatory and analgesic drugs although they also induce unwanted side e ects due to the inhibition of the physiological e ects regulated by prostaglandins. This has led to the search for new compounds with fewer side e ects, such as the nitro-NSAIDs (NO-NSAIDs). Paracetamol is an analgesic drug devoid of some of the side e ect of the NSAIDs but without anti-in¯ammatory activity. NCX-701 is a nitric oxide releasing version of paracetamol with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 28 publications
3
42
0
Order By: Relevance
“…For NCX-701, the dose was less than half of that observed to be effective in preliminary experiments, and even lower than the minimum effective dose observed after i.v. administration in electrophysiological experiments (Romero-Sandoval et al, 2002). This suggests that the interaction occurred within the subanalgesic dose range, supporting the results observed in electrophysiological experiments.…”
Section: Discussionsupporting
confidence: 88%
“…For NCX-701, the dose was less than half of that observed to be effective in preliminary experiments, and even lower than the minimum effective dose observed after i.v. administration in electrophysiological experiments (Romero-Sandoval et al, 2002). This suggests that the interaction occurred within the subanalgesic dose range, supporting the results observed in electrophysiological experiments.…”
Section: Discussionsupporting
confidence: 88%
“…The experiments are performed in a less traumatic preparation than that needed in other techniques which, for example, require laminectomy and full exposition of the spinal cord, avoiding artificial and extra nociceptive inputs. The experiments are, in this case, carried out in a much more similar conditions and data are very reproducible [27,29,38-40]. …”
Section: Discussionmentioning
confidence: 99%
“…Some studies, for example, have shown a clear relationship between retinoic acid and the generation of nitric oxide (NO) [9,12,28], prostaglandins [4,11] and the expression of cyclooxigenase 1 (COX-1) [23] and COX-2 [14,17]. All these mediators are involved in the generation or maintenance of sensitization and pain due to inflammation and are the targets for many painkillers studied in our lab among many others [7,10,26].…”
Section: Introductionmentioning
confidence: 98%